EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS IV DI SDN 44 MANDE KOTA BIMA: EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS IV DI SDN 44 MANDE KOTA BIMA - julfa Aulia; Ihsan; Miftahul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effectiveness of the Project Based Learning (PjBL) model in improving the creative thinking skills of fourth-grade students at SDN 44 Mande Kota Bima. The research employed a one-group pretest–posttest design involving 24 students. The instrument used was a creative thinking ability test administered before and after the treatment. Data analysis was conducted through normality test, homogeneity test, and paired sample t-test using SPSS. The findings revealed that the average pretest score of 62.5 increased to 82.3 in the posttest. The results of the normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The paired sample t-test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. The N-Gain score of 0.53 was categorized as moderate. Therefore, it can be concluded that the implementation of the Project Based Learning model is effective in enhancing students’ creative thinking skills, particularly in Civic Education learning.